Analyzing The Use of The Year Four, Theme Three Student Book of the 2013 Curriculum to Build Environmental Awareness - Mentari Deka Handayani; Laili Etika Rahmawati; Yeny Prastiwi; Eko Supriyanto; Choiriyah Widyasari (Universitas Muhammadiyah Surakarta, 2021)
The 2013 Curriculum emphasizes the cultivation of individual values. There are 18 values to be instilled, one of which is caring for the environment. These values are taught through daily teaching and learning activities. Environmental awareness is discussed in the year four student book under theme three. This research is designed as a descriptive-qualitative study facilitating document study. Data collection was done using the data analysis technique, content analysis. The validity of the data was tested using semantic validity and stability reliability. Results showed that the value of environmental awareness was present in theme three of the year four student book and can be divided into three indicators. These indicators include caring for plants, caring for animals as well as caring for other human beings. In conclusion, theme three of the year four student book is regarded as appropriate teaching material.